Analysis of Policies and Implementation of Railway Crossing Regulations in Indonesia: A Multi-Stakeholder Approach to Enhance Compliance and Safety - Ilham Ilham (West Science Information System and Technology, 2024)
This study examines the implementation of railway crossing regulations in Indonesia, employing a multi-stakeholder approach to enhance safety and compliance. Utilising a quantitative methodology, the research surveyed 500 respondents across various stakeholder groups. Structural Equation Modelling-Partial Least Squares analysis revealed that a multi-stakeholder approach significantly influences the effectiveness of regulation implementation (β = 0.68, p < 0.001). Inter-agency coordination emerged as the second most crucial factor (β = 0.55, p < 0.001), mediating the relationship between the multi-stakeholder approach and implementation effectiveness. The study also found a strong correlation between implementation effectiveness and regulatory compliance (β = 0.71, p < 0.001). Whilst community involvement and technology integration showed smaller influences, they remain significant contributors to implementation effectiveness. Notably, perceptions were consistent across stakeholder groups, indicating a shared understanding of key issues. The findings underscore the need for collaborative platforms in policy formulation and implementation, increased investment in technology and community engagement programmes, and adaptive regulatory frameworks that accommodate Indonesia's diverse contexts. This research contributes to the literature on transportation safety in developing countries and provides empirical evidence for policy reforms in railway crossing safety management in Indonesia.